Effect of superheated steam treatment on the structural and digestible properties of wheat flour. (March 2021) - Ma, Yongshuai; Xu, Dan; Sang, Shangyuan; Jin, Yamei; Xu, Xueming; Cui, Bo
Abstract: The structural and digestive properties of wheat flour which had been treated with superheated steam were investigated. Superheated steam treatment increased the degree of gelatinization (DG) and water absorption indexes (WAI) while decreased water solubility indexes (WSI) of wheat flour samples, compared with native wheat flour. The structural properties of wheat flour were characterized using scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM), particle size analyzer, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The starch granules agglomeration and denatured gluten proteins aggregation of samples were observed after treated with superheated steam. Additionally, Superheated steam treatment decreased the relative crystallinity and short-range order structure of starch. These structural changes were related to the starch digestibility. Superheated steam treatment caused the significant increase for slowly digestible starch (SDS) contents from 21.5% of native wheat flour to 35.0% of treated wheat flour (170 °C, 4 min). Additionally, the equilibrium hydrolysis concentration (C∞ ) and the kinetic coefficient (k) of treated wheat flour were lower than native wheat flour, indicating that superheated steam treatment decelerated the hydrolysis rate. These results contributed to the applications of superheated steam technology in wheat flour modification. Graphical abstract: Image 1 Highlights: Structure and digestibility properties of wheat flour were studied. Gluten aggregation of wheat flour was observed by superheated steam treatment. Superheated steam treatment changed the structural characteristics of wheat flour. Superheated steam treatment increased SDS and RS contents of wheat flour.